PTU-075 Reconfiguring a gastroenterology inpatient service – a success story. (June 2019) - Pathak, Suraj; Verma, Ajay
Abstract : Introduction: Studies have demonstrated that consultant delivered care can lead to; increases in productivity, reducing length of stay, and increasing patient satisfaction. 1 The Gastroenterology inpatient (IP) service at Kettering General Hospital was reconfigured to implement NHS improvement's SAFER patient flow bundle. 2 The incumbent arrangements on Deene C Ward (DCW) ; 29 patients under the care of three Consultants doing twice weekly ward rounds (WR) not prospectively covered, newly admitted and unwell patients reviewed by any WR as a safety net arrangement. This was transformed to a Digestive Diseases Unit (DDU), bed base reduced from 29 beds (3 side rooms, 3 x 6 bedded bays, a 5 bedded bay, & a 3 bedded bay), to 20 beds, by reducing 6 bedded bays to 4 beds, and converting the 3 bedded bay to a nurse-led Gastroenterology Treatment Area (GTA) for daycase ambulatory patients. This facilitated the introduction of a Consultant of the Week (CotW) model in November 2017. The CotW, for 2 weeks (prospectively covered), is responsible for daily DDU WRs of all 20 patients under their care, review of IP referrals, inreach into urgent care wards, and support of GTA. There is minimal outpatient (OP) commitment (no endoscopy lists or OP clinics). Outcomes were analysed at 12 months to assess the impact on patient care. Methods: A retrospective observational study was conducted to benchmark and evaluate changes in consultant led care. Patients were identified through electronic records. Data was collected from electronic discharge letters and paper notes. Statistical analysis was performed using Microsoft Excel. Results: GTA treating >90 patients & generating > £35K each month. Gastroenterology IP services SAFER compliant. Conclusion: The reconfiguration of Gastroenterology IP services has been a great success. A reduction in bed base (which many at management level were reticent about) has facilitated a CotW model of care to be implemented. The IP service is now SAFER compliant. Length of stay has significantly reduced by 26.2%. Weekly discharges per bed, and Consultant reviews, has significantly increased by 34.2% & 84.1% respectively. In addition, GTA treats >90 patients per month, generating income, preventing admissions, facilitating earlier discharges, and freeing capacity in the main hospital ambulatory unit. This reconfiguration shows that a CotW model of care is optimal, successful, and SAFER compliant, even if a bed base reduction is required to facilitate this. References: Academy of Medical Royal Colleges (2012) The benefits of consultant delivered care, 1st edn: AOMRC SAFER patient flow bundle https://improvement.nhs.uk/resources/safer-patient-flow-bundle-implement/